3rd International Symposium on Mathematical Sciences and Computing Research 2018 (ISMSC 2018) / Itaza Afiani Mohtar - Mohtar, Itaza Afiani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On November 13, 2018, the 3rd International Sym-posium on Mathematical Sciences and Computing Research 2018 (iSMSC 2018) was successfully organ-ised by the Faculty of Computer and Mathematical Sciences (FSKM) and the Faculty of Science and Infor-mation Technology (FSIT), Universiti Teknologi Petronas (co-organiser) at UiTM Perak Branch, Tapah Campus. The objectives of coordinating the symposium were to provide a venue for researchers, academia as well as participants to meet and exchange ideas on recent research and development in the areas of computing technology, information systems and mathematical sciences. It also functions as a platform to offer op-portunities for the participants to discuss the current research on a broad range of subjects. The sympo-sium attracted more than 30 paper submissions. Each submission underwent the double blind review process and 27 accepted papers were published in the Scopus Indexed International Journal of Engineering and Technology (IJET) Special Issue 33, Volume 7.